PENGARUH TINGKAT PENDIDIKAN DAN PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA SEKOLAH DASAR NEGERI 4 DAMAR KABUPATEN BELITUNG TIMUR - Jumi, Jumi; Santosa, Cecep Anwar Hadi Firdos; Rumanta, Maman (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
The low level of parental education is the cause of students dropping out of school. There are still many students who drop out of school because parents tend to pay less attention to the education of students, do not provide adequate learning facilities at home. Student learning motivation can be influenced by several factors, including the level of parental education and parental attention. This study aims to determine: (1) the effect of parental education level on the learning motivation of students at SDN 4 Damar, East Belitung Regency (2) the effect of parents' attention on the motivation of students at SDN 4 Damar, East Belitung Regency (3) the influence of education level and the attention of parents of students together on the learning motivation of students at SDN 4 Damar, East Belitung Regency. This research is a quantitative research with data collected by questionnaires and documentation. The sample of this study based on the slovin formula obtained as many as 60 students. Data analysis used descriptive percentage analysis and multiple regression analysis with the help of SPSS. The results of multiple regression analysis obtained the equation = 25,878+ 1,817 X1 + 0,702 X2. Multiple regression test obtained F count variable influence of parental education level of 4,224 so that the level of parental education on learning motivation is accepted. The variable of the influence of parental attention is obtained by F count of 6,968, so that parents' attention to learning motivation is accepted. The results of the simultaneous test (F test) obtained Fcount = 32,178, so that the level of parents' education and parents' attention to learning motivation was accepted. Variable level of parental education and parental attention simultaneously affect the motivation to learn by 53%. The conclusion of this study is that the level of parental education and parental attention affect the learning motivation of students at SDN 4 Damar, East Belitung Regency, either partially or simultaneously.